2021
DOI: 10.1039/d1ra01989a
|View full text |Cite
|
Sign up to set email alerts
|

Natural coumarins as potential anti-SARS-CoV-2 agents supported by docking analysis

Abstract: Potential of coumarins against Covid-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 35 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…An independent docking analysis also revealed that glycycoumarin (77) and isodispar B (78) were promising coumarins against COVID-19 virus (Figure 18). 88 Moreover, a few additional coumarins were proposed to be potential protease inhibitors of COVID-19 virus as revealed by in silico molecular docking. 89 The prediction by these computational methods underscores the importance of chromene (72) and coumarin (73) core structures as antiviral drug candidates.…”
Section: Antiviral Alkaloids and Alkaloid-like Compounds Against Covi...mentioning
confidence: 99%
See 2 more Smart Citations
“…An independent docking analysis also revealed that glycycoumarin (77) and isodispar B (78) were promising coumarins against COVID-19 virus (Figure 18). 88 Moreover, a few additional coumarins were proposed to be potential protease inhibitors of COVID-19 virus as revealed by in silico molecular docking. 89 The prediction by these computational methods underscores the importance of chromene (72) and coumarin (73) core structures as antiviral drug candidates.…”
Section: Antiviral Alkaloids and Alkaloid-like Compounds Against Covi...mentioning
confidence: 99%
“…, and dihydroergotamine (88) product, toxoflavin (86) (Figure 20), isolated from Gram-negative bacteria, Burkholderia gladioli and Burkholderia glumae, 101,102 and it was reported to have broad-spectrum of antifungal activity. 102 Fascaplysin ( 84) is a marine natural product, which was isolated as an antimicrobial pigment from the marine sponge Fascaplysinopsis sp.…”
Section: Antiviral Alkaloids and Alkaloid-like Compounds Against Covi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Scopoletin, rutin, quercetin and kaempferol are present in noni fruit and juice [32] [33]. In silico studies (computer modeling or simulation) have revealed that scopoletin and related compounds have structural properties that allow it to bind to and inhibit SARS-CoV-2 main protease (Mpro) as well as interact with ACE2, thereby interfering with spike protein-ACE2 recognition [34] [35] [36]. Rutin exhibited potent spike protein binding and anti-Mpro activity in molecular docking studies [37] [38].…”
Section: Sars-cov-2 Spike Protein-ace2 Binding Inhibition Assaymentioning
confidence: 99%
“…We investigated the antiviral activity of the isolated compound against SARS-CoV-2 together with other compounds isolated in our previous study [ 15 ] including four naphthopyrones, namely, flavasperone ( 1 ), rubrofusarin B ( 2 ), aurasperone A ( 3 ), fonsecinone A ( 4 ) and aspernigrin A alkaloid ( 5 ). Several in silico techniques, including molecular docking, molecular dynamics simulations (MDS), and end-state thermodynamics, are widely used as valuable tools for explaining the biological activities and the binding ability of the tested molecules to important therapeutic targets [ 16 , 17 , 18 ]. SARS-CoV-2 has two proteases, the main protease (M pro ), and the papain-like protease (PL pro ), which are essential for processing the viral non-functional proteins, and they are among the most important therapeutic targets used for the treatment of COVID-19 [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%